Flexible and lightweight MXene/silver nanowire/polyurethane composite foam films for highly efficient electromagnetic interference shielding and photothermal conversion. (20th October 2021) - Cheng, Ying; Lu, Ying; Xia, Ming; Piao, Longhai; Liu, Qingzhen; Li, Mufang; Zhou, Yang; Jia, Kangyu; Yang, Liyan; Wang, Dong
Abstract: Dual functional composite films with high electromagnetic interference (EMI) shielding and photothermal conversion properties are urgently demanded for modern microelectronic devices, especially to be used in an extreme environment. Here, flexible and lightweight MXene/AgNW/PU composite foam films were constructed by incorporating 1D AgNWs and 2D MXene in a PU matrix for highly efficient electromagnetic interference shielding and photothermal conversion. The 3D conductive network of AgNWs and MXene as well as the porous structure with multiple interfaces facilitated a high shielding effectiveness of 50 dB at a low density of 0.15 g/cm 3 in X-band with a high absorption-dominated shielding efficiency of 86%. In the frequency of Ku-band, the composite foam film presented a higher shielding efficiency of 60 dB with the absorption efficiency as high as 95%, representing an excellent absorption-dominated shielding performance. The composite foam film remained an excellent EMI shielding efficiency of 41.5 dB after 1000 cycles of compression and release. Furthermore, the composite foam film showed a high photothermal conversion property. The flexible and lightweight MXene/AgNW/PU composite foam films provided a facile strategy for applications of EMI shielding and photothermal conversion in aerospace as well as portable smart electronics. Graphical abstract: Image 1